Application of eDNA Technology to Assess Phytoplankton Diversity in the Ciliwung Downstream Area, Jakarta, Indonesia - Permatasari, Prita Ayu; Aprilia, Mita; Effendi, Hefni; Zainalarifin, Jauhar (Media Konservasi, 2025)
Rivers have the potential for enormous flows of water, nutrients, and food that can create habitats for various living creatures. However, the flow of pollutants into estuaries and coastal areas can degrade environmental conditions in downstream areas of the river. Numerous studies have highlighted the loss of aquatic species due to increased stressors and pollutants in heavily contaminated rivers. This manuscript aims to analyze the phytoplankton diversity in three stations (natural riparian, concreted riparian, and estuary) of the Ciliwung River in Jakarta. Using environmental DNA (eDNA), we identified and compared the number of phytoplankton families and read sequences with various water quality parameters. The results showed that each station consists of 16, 13, and 20 families with 11,257; 75,963; and 37,339 read sequences, respectively. The study showed that phytoplankton family diversity in Stations 1 and 2 correlates with water pollution levels (lightly to extremely polluted). In contrast, Station 3 exhibited an unusual pattern, with high family diversity despite declining water quality.